Factors related to autonomy among Lebanese women: a web-based cross-sectional study - Sandrella Bou Malhab; Hala Sacre; Diana Malaeb; Nathalie Lahoud; Dalia Khachman; Joelle Azzi; Chadia Haddad; Pascale Salameh (BMC, 2021)
Abstract Background Autonomy involves making independent decisions and creating lasting and equitable power relationships within families. Many factors, dependent on both the woman and her partner, can influence self-dependence, and subsequent decision-making, exerting a protective or triggering effect on its development. Therefore, the primary objective of the study was to assess autonomy in a sample of Lebanese women. The secondary objective was to evaluate the association between socioeconomic status, psychological factors, and autonomy. Methods A web based cross-sectional online study was conducted between June 8 and August 1, 2020. The questionnaire developed on Google Forms was distributed through social media and WhatsApp groups, using the snowball technique. The Women's Autonomy Index (WAI) was created using three items adapted from a previous study. In addition, the Composite Abuse Scale Revised-Short Form (CASR-SF) was used to assess three domains of abuse: physical, sexual, and psychological. The Perceived stress scale short version to measure stress perception, the Lebanese Anxiety Scale to measure anxiety and the Patient Health Questionnaire (PHQ-9) to assess depression. The Statistical Package for the Social Sciences (SPSS) software version 25 was used for data analysis. Linear regressions were performed, taking the Women's Autonomy Index as the dependent variable. Results The sample consisted of 369 Lebanese women. University education level (beta = 1.263), alcohol consumption (beta = 0.586), intermediate income level (beta = 0.702), high income (beta = 0.911), employment (beta = 0.559), and older age (beta = 0.033) were significantly associated with higher WAI. Living in South Lebanon (beta = − 0.668) and being Druze (beta = − 323) were associated with lower WAI. Significantly higher mean scores of anxiety and perceived stress were found among women with low autonomy. Conclusion In Lebanon, the autonomy of women depends on several personal and partner-related characteristics (education, socioeconomic status, age), in addition to the cultural (geographic and religious) environment. Furthermore, low autonomy is associated with higher perceived stress and anxiety and probable depression and domestic abuse.